University tutorials and learning through competences. How can these objectives be achieved? - Rufino Cano González (Revista Electrónica Interuniversitaria de Formación del Profesorado)
For a decade, a great number of countries have been immersed and have been actively participating in a common convergence scenario in Higher Education. In this scenario interesting, innovative proposals, which have reached a joint consensus, have been proposed. These proposals, which we hope are academically well designed, will entail and are already entailing a number of deep changes and other adjustments stemming from the creation and subsequent development of new university qualifications (Degree, Master, Doctorate). They also call for the use of different active methodologies which allow to go deeper into the construction, personalization and facilitation of students’ learning. This is viewed as essential to get intellectual and academic quality training, to attain a better and more balanced daily intervention in the different Higher Education contexts and finally to develop professional practice in a responsible and balanced way, a practice for which one has been trained regardless of one’s personal-academic profile.